Fellowship Point : a novel [large type] - Dark, Alice Elliott (Thorndike Press large print basic series., 2022)
"Celebrated children's book author Agnes Lee is determined to secure her legacy--to complete what she knows will be the final volume of her pseudonymously written Franklin Square novels; and even more consuming, to permanently protect the peninsula of majestic coast in Maine known as Fellowship Point. To donate the land to a trust, Agnes must convince shareholders to dissolve a generations-old partnership. And one of those shareholders is her best friend, Polly. Polly Wister has led a different kind of life than Agnes: that of a well-off married woman with children, defined by her devotion to her husband, and philosophy professor with an inflated sense of stature. She exalts in creating beauty and harmony in her home, in her friendships, and in her family. Polly soon finds her loyalties torn between the wishes of her best friend and the wishes of her three sons--but what is it that Polly wants herself? Agnes's designs are further muddied when an enterprising young book editor named Maud Silver sets out to convince Agnes to write her memoirs. Agnes's resistance cannot prevent long-buried memories and secrets from coming to light with far-reaching repercussions for all. Fellowship Point reads like a classic 19th-century novel in its beautifully woven, multilayered narrative, but it is entirely contemporary in the themes it explores; a deep and empathic interest in women's lives, the class differences that divided us, the struggle to protect the natural world, and, above all, a reckoning with intimacy, history, and posterity. It is a masterwork from Alice Elliott Dark"--